A review of the German mandatory deposit for one-way drinks packaging and drinks packaging taxes in Europe - Markus Groth (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2008)
The mandatory deposit for one-way drinks packaging, embodied in the German Packaging Ordinance of 1991, entered into force in January 2003, after the condition for its implementation was given by the fall of the market share of reusable drinks packaging under 72% in 1997. In this context the author doubts that the German mandatory deposit is an effective instrument to stabilise the market share of ecologically advantageous drinks packaging. Rather it is to be expected that the environmental policy objectives can be accomplished more effectively by a reorientation of the specific environmental policy. Hence it needs to be considered that even eleven years after the first time decrease of the relevant market share of reusable drinks packaging an urgent need for action exists in Germany. This practise based analysis therefore deals with packaging-taxes as an alternative environmental policy instrument and points out recommendations against the background of a further amending of the German Packaging Ordinance as well as experiences from the use of packaging taxes in Europe.
Keywords: C93; D44; D82; H41; L14; Q24; Q28; Q57; R52; 330; Packaging tax; waste management; mandatory deposit; non-ecologically advantageous one-way drinks packaging; environmental policy; Getränkeverpackung; Abfallabgabe; Wirtschaftspolitische Wirkungsanalyse; Mehrwegverpackung; Umweltorientierte Verpackung; Umweltabgabe; Deutschland; Europa